Evaluation of total phenolic content and antioxidant activities from different type of extraction technique of Helianthus tuberosus - Alias, Nur Diyana; Puteh, Fadzilah; Mohd Zulkifli, Nurin Izzati; Noor Hasnan, Noor Zafira (HH Publisher, 2021)
This study investigated the difference of antioxidants activity from different extraction techniques of Jerusalem artichoke (Helianthus tuberosus). Three different extraction techniques involved were aqueous extraction, high-pressure steam extraction and 70% ethanol extraction. Total phenolic content (TPC) was determined using the Folin-Ciocalteu method. The antioxidant activities were analysed using ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH). The high-pressure steam extract showed the highest total phenolic content and both FRAP and DPPH activities at 127.87 ± 0.08 mg GAE/g, 53.38 ± 2.76 mg AAE/g and 79.92 ± 0.26 mg AAE/g. Meanwhile, the aqueous extract showed 2-fold higher of total phenolic content compared to ethanol extract at 65.73 ± 9.44 and 30.61 ± 0.00 mg GAE/g. Conversely, antioxidant activities obtained from ethanol extracts (41.49 ± 2.54 and 41.10 ± 0.10 mg AAE/g.) were higher compared to aqueous extract (23.29 ± 0.47 and 5.24 ± 0.38 mg AAE/g.). This study suggests that different extraction methods influenced the findings of total phenolic content and antioxidant activities of the Jerusalem artichoke. Hence, Jerusalem artichoke can be considered as a potential source of natural antioxidants.